Sulfur and Oxygen Isotope Records of Sulfate-Driven Anaerobic Oxidation of Methane in Diffusion-Dominated Marine Sediments - Chen, Tingting; Strauss, Harald; Fang, Yunxin; Lin, Zhiyong; Sun, Xiaoming; Liu, Jiarui; Lu, Yang; Yang, Xin; Lin, Haixin; Wu, Zhongwei; Lin, Xiao (Frontiers in Earth Science, 2022)
Organoclastic sulfate reduction (OSR) and sulfate-driven anaerobic oxidation of methane (SD-AOM) are the two major microbial pathways for sulfate consumption in marine sulfur cycle. The relative changes of sulfur and oxygen isotope ratios in pore water sulfate are affected by the mode of microbial sulfate reduction and have been applied as an indicator for assessing methane excess environments. However, so far, this isotope proxy fails to distinguish sulfate reduction processes fueled by the oxidation of organic matter or by diffusing methane. To better understand the mechanism of sulfur and oxygen isotope partitioning during OSR and SD-AOM, coupled sulfur and oxygen isotopic compositions of pore water sulfate (δ34SSO4 and δ18OSO4) were investigated from four methane diffusing sites (CL56, CL57, CL59, and CL60) of the South China Sea, supplemented by carbon isotopic composition of dissolved inorganic carbon (DIC) and sulfur isotopic composition of pyrite in bulk sediments. Pore water sulfate and DIC concentrations, as well as calculated net sulfate reduction rates suggest that the sulfate reduction at site CL57 was mainly dominated by OSR, whereas sites CL56, CL59, and CL60 were likely impacted by both OSR and SD-AOM. Furthermore, the trend of cross-plotting δ18OSO4 versus δ34SSO4 values from site CL57 was distinguishable from sites CL56, CL59, and CL60, although all study sites show similar patterns to those derived from methane limited environments. This further indicates the trajectory of sulfur and oxygen isotope partitioning was affected by the mode of sulfate reduction (i.e., OSR vs. SD-AOM). At site CL57, the low net sulfate reduction rate would lead to enhanced oxidation of intermediate sulfur species during OSR, thus leading to a higher slope in the δ18OSO4 versus δ34SSO4 cross-plot (1.26). In contrast, the higher net sulfate reduction rates at sites CL56, CL59, and CL60 due to the impact from SD-AOM would lead to a lower slope in the δ18OSO4 versus δ34SSO4 cross-plots (0.78 ± 0.11). This study provides new insights into the sulfur and oxygen isotope systematics during microbial sulfate reduction processes in methane diffusing environments.